A particle refining agent for 7 series aluminum-zinc alloy
By using matrix such as potassium chloride, calcium fluoride, magnesium chloride in the refining agent of 7-type aluminum-zinc alloy, and adding graphene modifiers and modifiers based on modified sols, the performance of existing refining agents is solved. The problem has achieved higher hydrogen removal and slag removal effects and improved aluminum-zinc alloy performance.
Patent Information
- Application Number
- CN202411774876.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The refining agents of the existing 7-series aluminum-zinc alloy have poor hydrogen removal and slag removal performance, and the strength and elongation performance of the aluminum-zinc alloy are not significantly improved, making it difficult to optimize corrosion resistance and heat resistance stability.
Potassium chloride, calcium fluoride and magnesium chloride are used as the refining agent matrix, and graphene modifiers and modified sol-based toners are added. Through ultrasonic modification treatment and ball milling, heat treatment is coordinated to optimize the activity performance of graphene. .
The hydrogen removal rate and slag removal rate performance are significantly optimized, the strength and elongation performance of aluminum-zinc alloy are improved, and the corrosion resistance and heat resistance of the product are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of particle refining agents, and in particular to a particle refining agent for 7 series aluminum-zinc alloys. Background Art
[0002] 7075 refers to a commonly used alloy in the 7 series aluminum alloy. Among the more common aluminum alloys, 7075 alloy has the best strength and is commonly used in parts manufactured by CNC cutting. It is suitable for aircraft frames and high-strength accessories. The refining agent is a white powder or granular flux, which is made by drying and mixing a variety of inorganic salts in a certain proportion. It is mainly used to remove hydrogen and floating oxide inclusions in the aluminum liquid.
[0003] The existing refining agent for 7 series aluminum-zinc alloy has poor dehydrogenation rate and slag removal rate performance, and does not significantly improve the strength and elongation performance of the aluminum-zinc alloy, and it is difficult to optimize the corrosion resistance and heat resistance stability of the product. Based on this, the present invention further improves it. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a particle refining agent for 7 series aluminum-zinc alloy to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a granular refining agent for 7 series aluminum-zinc alloy, comprising the following raw materials in parts by weight:
[0007] 35-45 parts of potassium chloride, 10-15 parts of calcium fluoride, 7-11 parts of graphene modifier, 6-8 parts of modifier based on modified sol, 5-8 parts of magnesium chloride;
[0008] The preparation method of the graphene modifier is:
[0009] S01: Stir graphene in a sufficient amount of hydrogen peroxide solution to mix thoroughly, then wash, filter and dry;
[0010] The dried graphene was heat treated at 150-160°C for 10-15 min, then heated to 300°C at a rate of 2-5°C / min, kept at that temperature for 10 min, and finally air-cooled to room temperature;
[0011] S02: Preparation of additives:
[0012] S021: first prepare a chitosan solution with a mass fraction of 3-5%;
[0013] S022: adding 2 to 5 parts of cerium powder and 1 to 3 parts of sodium dodecylbenzene sulfonate to 5 to 8 parts of chitosan solution and stirring evenly, then adding 4 to 7 parts of nano carbon powder and blending thoroughly, then filtering and drying to obtain an additive;
[0014] S03: adding 2 to 5 parts of silane coupling agent KH550, 1 to 3 parts of lanthanum chloride solution and 4 to 6 parts of additives to 5 to 8 parts of sodium silicate solution and stirring thoroughly to obtain a modified coupling solution;
[0015] S04: the graphene in S01 is sent to a modified coupling liquid with a volume of 4 to 6 times the total volume of the graphene in S01 for ultrasonic modification treatment, and after the ultrasonic treatment is finished, the graphene is filtered and dried to obtain a graphene modifier;
[0016] The preparation method of the modified sol-based toner is:
[0017] S101: yttrium oxide and nano-silicon dioxide are fully mixed in a weight ratio of 2:(4-6), and then the mixture is placed in a sufficient amount of sodium alginate solution and dispersed evenly to obtain a yttrium-silicon compounding agent;
[0018] S102: The modified sol and yttrium-silicon compound adjusting agent are mixed in a weight ratio of 3:5 and subjected to ball milling treatment at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a adjusting agent based on the modified sol.
[0019] Preferably, the particle refining agent comprises the following raw materials in parts by weight:
[0020] 40 parts of potassium chloride, 12.5 parts of calcium fluoride, 9 parts of graphene modifier, 7 parts of a modifier based on modified sol, and 4 parts of magnesium chloride.
[0021] Preferably, the mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the sodium silicate solution is 4-6%.
[0022] Preferably, the ultrasonic power of the ultrasonic modification treatment is 350-400 W, and the ultrasonic time is 20-30 min.
[0023] Preferably, the mass fraction of the sodium alginate solution is 5-8%.
[0024] Preferably, the modified sol comprises the following raw materials in parts by weight:
[0025] 3-5 parts of nano silica sol, 4-6 parts of dopamine hydrochloride solution, 2-3 parts of nano titanium dioxide, 0.4-0.5 parts of fly ash and 1-2 parts of stearic acid.
[0026] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%.
[0027] The use of refining agent is as follows:
[0028] The 7 series aluminum-zinc alloy is completely melted to obtain aluminum-zinc alloy liquid, and nitrogen is introduced. The nitrogen introduction time is 20 minutes, and the nitrogen introduction amount is 10% of the total amount of the aluminum-zinc alloy liquid;
[0029] Then, the granular refining agent and the aluminum-zinc alloy liquid are mixed and refined in a weight ratio of 1:30 for 20 minutes. After the refining is completed, the refined liquid is sent into a mold for cooling and forming to obtain a refined aluminum-zinc alloy.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The particle refining agent of the present invention uses potassium chloride, calcium fluoride and magnesium chloride as the refining agent matrix, and a graphene modifier and a modified sol-based modifier are added to coordinate and cooperate with each other. The obtained refining agent product can optimize the hydrogen removal rate and slag removal rate performance, and at the same time has a significant effect on improving the strength and elongation performance of the aluminum-zinc alloy, and optimizes the corrosion resistance and heat resistance stability of the product;
[0032] 2. The graphene modifier uses graphene treated with a hydrogen peroxide solution, then heat treated at 150-160°C for 10-15 minutes, and then heated to 300°C at a rate of 2-5°C / min, and kept warm for 10 minutes. The active efficiency of graphene is optimized through coordinated thermal improvement treatment, and the modified coupling liquid is ultrasonically modified. The modified coupling liquid is treated with a silane coupling agent KH550, a lanthanum chloride solution and a sodium silicate solution, and the performance of the product is further improved;
[0033] 3. The added additives are coordinated in the modified coupling liquid system, and the coordination of graphene is improved through the coordination and synergy between the raw materials. The cerium powder, sodium dodecylbenzene sulfonate in the additives are fully blended with the chitosan solution and nano-carbon powder. The raw materials in the additives are coordinated and enhanced with each other, so that the additives are reinforced in the modified coupling liquid. The coordination and synergy between the raw materials further enhances the effect of the graphene modifier in the system, thereby improving the product's optimized hydrogen removal rate and slag removal rate performance, as well as improving the strength and elongation performance of the aluminum-zinc alloy and the corrosion resistance and heat resistance stability of the product;
[0034] 4. The modified sol-based conditioning agent uses yttrium oxide and nano-silicon dioxide as base materials, which are improved by dispersion in sodium alginate solution and then improved by ball milling with a modified sol. The nano-silica sol, dopamine hydrochloride solution, nano-titanium dioxide, fly ash and stearic acid in the modified sol are blended and coordinated. The fly ash is combined with nano-titanium dioxide, and then the raw materials such as nano-silicon sol are blended and coordinated to further improve the yttrium-silicon complex conditioning agent. The obtained modified sol-based conditioning agent has a better coordination effect with the graphene modifier, thereby further improving the product performance. DETAILED DESCRIPTION
[0035] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] A particle refining agent for 7 series aluminum-zinc alloy of this embodiment includes the following raw materials in parts by weight:
[0037] 35-45 parts of potassium chloride, 10-15 parts of calcium fluoride, 7-11 parts of graphene modifier, 6-8 parts of modifier based on modified sol, and 5-8 parts of magnesium chloride.
[0038] The particle refining agent of this embodiment includes the following raw materials in parts by weight:
[0039] 40 parts of potassium chloride, 12.5 parts of calcium fluoride, 9 parts of graphene modifier, 7 parts of a modifier based on modified sol, and 4 parts of magnesium chloride.
[0040] The preparation method of the graphene modifier of this embodiment is:
[0041] S01: Stir graphene in a sufficient amount of hydrogen peroxide solution to mix thoroughly, then wash, filter and dry;
[0042] The dried graphene was heat treated at 150-160°C for 10-15 min, then heated to 300°C at a rate of 2-5°C / min, kept at that temperature for 10 min, and finally air-cooled to room temperature;
[0043] S02: Preparation of additives:
[0044] S021: first prepare a chitosan solution with a mass fraction of 3-5%;
[0045] S022: adding 2 to 5 parts of cerium powder and 1 to 3 parts of sodium dodecylbenzene sulfonate to 5 to 8 parts of chitosan solution and stirring evenly, then adding 4 to 7 parts of nano carbon powder and blending thoroughly, then filtering and drying to obtain an additive;
[0046] S03: adding 2 to 5 parts of silane coupling agent KH550, 1 to 3 parts of lanthanum chloride solution and 4 to 6 parts of additives to 5 to 8 parts of sodium silicate solution and stirring thoroughly to obtain a modified coupling solution;
[0047] S04: The graphene in S01 is sent to a modified coupling liquid with a volume of 4 to 6 times the total volume of the graphene in S01 for ultrasonic modification treatment. After the ultrasonic treatment is finished, the graphene is filtered and dried to obtain a graphene modifier.
[0048] The mass fraction of the lanthanum chloride solution in this embodiment is 3-5%; the mass fraction of the sodium silicate solution is 4-6%.
[0049] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350-400 W, and the ultrasonic time is 20-30 min.
[0050] The preparation method of the modified sol-based toner of this embodiment is:
[0051] S101: yttrium oxide and nano-silicon dioxide are fully mixed in a weight ratio of 2:(4-6), and then the mixture is placed in a sufficient amount of sodium alginate solution and dispersed evenly to obtain a yttrium-silicon compounding agent;
[0052] S102: The modified sol and yttrium-silicon compound adjusting agent are mixed in a weight ratio of 3:5 and subjected to ball milling treatment at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a adjusting agent based on the modified sol.
[0053] The mass fraction of the sodium alginate solution in this embodiment is 5-8%.
[0054] The modified sol agent of this embodiment includes the following raw materials in parts by weight:
[0055] 3-5 parts of nano silica sol, 4-6 parts of dopamine hydrochloride solution, 2-3 parts of nano titanium dioxide, 0.4-0.5 parts of fly ash and 1-2 parts of stearic acid.
[0056] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%.
[0057] Embodiment 1:
[0058] A particle refining agent for 7 series aluminum-zinc alloy of this embodiment includes the following raw materials in parts by weight:
[0059] 35 parts of potassium chloride, 10 parts of calcium fluoride, 7 parts of graphene modifier, 6 parts of modifier based on modified sol, and 5 parts of magnesium chloride.
[0060] The preparation method of the graphene modifier of this embodiment is:
[0061] S01: Stir graphene in a sufficient amount of hydrogen peroxide solution to mix thoroughly, then wash, filter and dry;
[0062] The dried graphene was heat treated at 150 °C for 10 min, then heated to 300 °C at a rate of 2 °C / min, kept at that temperature for 10 min, and finally air-cooled to room temperature;
[0063] S02: Preparation of additives:
[0064] S021: first prepare a chitosan solution with a mass fraction of 3%;
[0065] S022: adding 2 parts of cerium powder and 1 part of sodium dodecylbenzene sulfonate to 5 parts of chitosan solution and stirring evenly, then adding 4 parts of nano carbon powder and blending thoroughly, then filtering and drying to obtain an additive;
[0066] S03: adding 2 parts of silane coupling agent KH550, 1 part of lanthanum chloride solution and 4 parts of additives to 5 parts of sodium silicate solution and stirring thoroughly to obtain a modified coupling solution;
[0067] S04: The graphene in S01 is sent to a modified coupling liquid with a volume of 4 times the total amount of the graphene in S01 for ultrasonic modification. After the ultrasonic treatment is finished, the graphene is filtered and dried to obtain a graphene modifier.
[0068] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the sodium silicate solution is 4%.
[0069] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350W, and the ultrasonic time is 20min.
[0070] The preparation method of the modified sol-based toner of this embodiment is:
[0071] S101: yttrium oxide and nano-silicon dioxide are fully mixed in a weight ratio of 2:4, and then the mixture is placed in a sufficient amount of sodium alginate solution and dispersed evenly to obtain a yttrium-silicon compounding agent;
[0072] S102: The modified sol and yttrium-silicon compound adjusting agent are mixed in a weight ratio of 3:5 and subjected to ball milling treatment at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a adjusting agent based on the modified sol.
[0073] The mass fraction of the sodium alginate solution in this embodiment is 5%.
[0074] The modified sol agent of this embodiment includes the following raw materials in parts by weight:
[0075] 3 parts of nano silica sol, 4 parts of dopamine hydrochloride solution, 2 parts of nano titanium dioxide, 0.4 parts of fly ash and 1 part of stearic acid.
[0076] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%.
[0077] Embodiment 2:
[0078] A particle refining agent for 7 series aluminum-zinc alloy of this embodiment includes the following raw materials in parts by weight:
[0079] 45 parts of potassium chloride, 15 parts of calcium fluoride, 11 parts of graphene modifier, 8 parts of toner based on modified sol, and 8 parts of magnesium chloride.
[0080] The preparation method of the graphene modifier of this embodiment is:
[0081] S01: Stir graphene in a sufficient amount of hydrogen peroxide solution to mix thoroughly, then wash, filter and dry;
[0082] The dried graphene was heat treated at 160 °C for 15 min, then heated to 300 °C at a rate of 5 °C / min, kept at that temperature for 10 min, and finally air-cooled to room temperature;
[0083] S02: Preparation of additives:
[0084] S021: first prepare a chitosan solution with a mass fraction of 5%;
[0085] S022: adding 5 parts of cerium powder and 3 parts of sodium dodecylbenzene sulfonate to 8 parts of chitosan solution and stirring evenly, then adding 7 parts of nano carbon powder and blending thoroughly, then filtering and drying to obtain an additive;
[0086] S03: adding 5 parts of silane coupling agent KH550, 3 parts of lanthanum chloride solution and 6 parts of additives to 8 parts of sodium silicate solution and stirring thoroughly to obtain a modified coupling solution;
[0087] S04: The graphene in S01 is sent to a modified coupling liquid with a volume of 6 times the total amount of the graphene in S01 for ultrasonic modification. After the ultrasonic treatment is finished, the graphene is filtered and dried to obtain a graphene modifier.
[0088] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the sodium silicate solution is 6%.
[0089] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.
[0090] The preparation method of the modified sol-based toner of this embodiment is:
[0091] S101: yttrium oxide and nano-silicon dioxide are fully mixed in a weight ratio of 2:6, and then the mixture is placed in a sufficient amount of sodium alginate solution and dispersed evenly to obtain a yttrium-silicon compounding agent;
[0092] S102: The modified sol and yttrium-silicon compound adjusting agent are mixed in a weight ratio of 3:5 and subjected to ball milling treatment at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a adjusting agent based on the modified sol.
[0093] The mass fraction of the sodium alginate solution in this embodiment is 8%.
[0094] The modified sol agent of this embodiment includes the following raw materials in parts by weight:
[0095] 5 parts of nano silica sol, 6 parts of dopamine hydrochloride solution, 3 parts of nano titanium dioxide, 0.5 parts of fly ash and 2 parts of stearic acid.
[0096] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%.
[0097] Embodiment 3:
[0098] A particle refining agent for 7 series aluminum-zinc alloy of this embodiment includes the following raw materials in parts by weight:
[0099] 40 parts of potassium chloride, 12.5 parts of calcium fluoride, 9 parts of graphene modifier, 7 parts of a modifier based on modified sol, and 4 parts of magnesium chloride.
[0100] The preparation method of the graphene modifier of this embodiment is:
[0101] S01: Stir graphene in a sufficient amount of hydrogen peroxide solution to mix thoroughly, then wash, filter and dry;
[0102] The dried graphene was heat treated at 155 °C for 12.5 min, then heated to 300 °C at a rate of 3.5 °C / min, kept at that temperature for 10 min, and finally air-cooled to room temperature;
[0103] S02: Preparation of additives:
[0104] S021: first prepare a chitosan solution with a mass fraction of 4%;
[0105] S022: adding 3.5 parts of cerium powder and 2 parts of sodium dodecylbenzene sulfonate to 6.5 parts of chitosan solution and stirring evenly, then adding 5.5 parts of nano carbon powder and blending thoroughly, then filtering and drying to obtain an additive;
[0106] S03: adding 3.5 parts of silane coupling agent KH550, 2 parts of lanthanum chloride solution and 5 parts of additives to 6.5 parts of sodium silicate solution and stirring thoroughly to obtain a modified coupling solution;
[0107] S04: The graphene in S01 is sent to a modified coupling liquid with a volume 5 times the total amount of the graphene in S01 for ultrasonic modification treatment. After the ultrasonic treatment is finished, the graphene is filtered and dried to obtain a graphene modifier.
[0108] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the sodium silicate solution is 5%.
[0109] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 370W, and the ultrasonic time is 25min.
[0110] The preparation method of the modified sol-based toner of this embodiment is:
[0111] S101: yttrium oxide and nano-silicon dioxide are fully mixed in a weight ratio of 2:5, and then the mixture is placed in a sufficient amount of sodium alginate solution and dispersed evenly to obtain a yttrium-silicon compounding agent;
[0112] S102: The modified sol and yttrium-silicon compound adjusting agent are mixed in a weight ratio of 3:5 and subjected to ball milling treatment at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a adjusting agent based on the modified sol.
[0113] The mass fraction of the sodium alginate solution in this embodiment is 6.5%.
[0114] The modified sol agent of this embodiment includes the following raw materials in parts by weight:
[0115] 4 parts of nano silica sol, 5 parts of dopamine hydrochloride solution, 2.5 parts of nano titanium dioxide, 0.45 parts of fly ash and 1.5 parts of stearic acid.
[0116] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%.
[0117] Comparative Example 1:
[0118] The difference from Example 3 is that no graphene modifier is added.
[0119] Comparative Example 2:
[0120] The difference from Example 3 is that step S01 is not used in the preparation of the graphene modifier.
[0121] Comparative Example 3:
[0122] The difference from Example 3 is that the modified coupling liquid treatment is not used in the preparation of the graphene modifier.
[0123] Comparative Example 4:
[0124] The difference from Example 3 is that no silane coupling agent KH550 or lanthanum chloride solution is added to the modified coupling liquid.
[0125] Comparative Example 5:
[0126] The difference from Example 3 is that no additive is added to the modified coupling liquid.
[0127] Comparative Example 6:
[0128] The difference from Example 3 is that no cerium powder or sodium dodecylbenzene sulfonate is added in the preparation of the additive.
[0129] Comparative Example 7:
[0130] The difference from Example 3 is that no nano carbon powder is added in the preparation of the additive and deionized water is used instead of the chitosan solution.
[0131] Comparative Example 8:
[0132] The difference from Example 3 is that no toner based on modified sol is added.
[0133] Comparative Example 9:
[0134] The difference from Example 3 is that no yttrium-silicon complexing agent is added in the preparation of the modifying agent based on the modified sol.
[0135] Comparative Example 10:
[0136] The difference from Example 3 is that no modified sol agent is added in the preparation of the modified sol-based toner.
[0137] The products of Examples 1-3 and Comparative Examples 1-10 were tested for hydrogen removal rate and slag removal rate, and the tensile strength, elongation improvement performance, and corrosion resistance and heat resistance stability were also tested:
[0138] Strength and elongation tests under normal conditions:
[0139] The 7 series aluminum-zinc alloy was used as the test matrix standard. The control group did not perform any operation. The experimental group completely smelted the 7 series aluminum-zinc alloy to obtain aluminum-zinc alloy liquid, and nitrogen was introduced for 20 minutes. The nitrogen introduction amount was 10% of the total amount of the aluminum-zinc alloy liquid.
[0140] Then, the granular refining agent and the aluminum-zinc alloy liquid are mixed and refined in a weight ratio of 1:30 for 20 minutes. After the refining is completed, the refined liquid is sent into a mold for cooling and forming to obtain a refined aluminum-zinc alloy.
[0141] By comparing the strength and elongation properties of the refined aluminum-zinc alloy with the 7-series aluminum-zinc alloy, the improvement rate of tensile strength and the improvement rate of elongation are calculated (e.g., improvement rate of tensile strength = strength of the refined aluminum-zinc alloy - strength of the 7-series aluminum-zinc alloy / strength of the 7-series aluminum-zinc alloy × 100%).
[0142] Tests of strength and elongation under corrosion and heat resistance conditions:
[0143] The 7 series aluminum-zinc alloy and the refined aluminum-zinc alloy were placed at 70°C for 12 hours, and then placed under 2% hydrochloric acid mist for 12 hours, and the performance of the products under heat resistance and acid corrosion resistance was tested. The specific test was based on the strength and elongation test methods under conventional conditions, and the tensile strength improvement rate and elongation improvement rate under heat resistance and acid corrosion resistance were obtained. The test results are shown in Table 1 below. Table 1 shows the performance tests of hydrogen removal rate, slag removal rate, strength and elongation.
[0144] Table 1 Performance tests of hydrogen removal rate, slag removal rate, strength and elongation
[0145]
[0146] It is obtained from Examples 1-3 and Comparative Examples 1-10:
[0147] The tensile strength improvement rate, elongation improvement rate, hydrogen removal rate and slag removal rate of the product of Example 3 of the present invention are coordinated and improved, and the performance stability of the product is remarkable under the conditions of heat resistance and acid corrosion resistance;
[0148] The present invention does not add a graphene modifier or a modifier based on modified sol, and the performance of the product has a significant trend of deterioration. The two are used in combination to achieve synergistic effects, and the product performance effect is most obvious.
[0149] The performance of the product showed a trend of deterioration when the S01 step was not used in the preparation of the graphene modifier, the modified coupling liquid was not used in the preparation of the graphene modifier, the silane coupling agent KH550 and the lanthanum chloride solution were not added to the modified coupling liquid, and the additives were not added to the modified coupling liquid. In addition, the performance of the product also showed a trend of deterioration when cerium powder and sodium dodecylbenzene sulfonate were not added in the preparation of the additive, nano-carbon powder was not added in the preparation of the additive, and deionized water was used instead of chitosan solution.
[0150] The additive obtained by the specific method of the present invention is combined with the specific raw materials in the modified coupling liquid, and the graphene modifier obtained by the S01 step has the most significant product performance effect. Other methods are not as obvious as the effect of the present invention.
[0151] When the yttrium-silicon compounding agent is not added in the preparation of the modified sol-based conditioning agent, and when the modified sol-based conditioning agent is not added in the preparation of the modified sol-based conditioning agent, the performance of the product also shows a trend of deterioration. At the same time, when the modified sol agent is not added, the performance of the product shows a more obvious trend of deterioration. The conditioning agent based on the modified sol obtained by combining the yttrium-silicon compounding agent and the modified sol agent obtained by the method of the present invention has the most significant product performance effect.
[0152] The composition of the modified sol has a significant impact on the performance of the product, so further research is needed:
[0153] Experimental Example 1:
[0154] The only difference from Example 3 is that no nano-silica sol is added to the modified sol.
[0155] Experimental Example 2:
[0156] The only difference from Example 3 is that no nano titanium dioxide is added to the modified sol.
[0157] Experimental Example 3:
[0158] The only difference from Example 3 is that fly ash is not added to the modified sol.
[0159] Experimental Example 4:
[0160] The only difference from Example 3 is that stearic acid is not added to the modified sol.
[0161] Experimental Example 5:
[0162] The only difference from Example 3 is that the dopamine hydrochloride solution in the modified sol is replaced by water.
[0163] The product performance tests of Experimental Examples 1-5 are shown in Table 2 below. Table 2 is a table showing the effects of the composition of the modified sol on the performance of the product.
[0164] Table 2 Effect of the composition of modified sol on product performance
[0165]
[0166] It can be seen from Experimental Examples 1-5 that fly ash and nano titanium dioxide are not added to the modified sol, and the product performance change trend has the greatest impact among the factors of the modified sol, followed by the absence of nano silica sol. At the same time, the absence of stearic acid in the modified sol and the use of water instead of dopamine hydrochloride solution in the modified sol all have a tendency to deteriorate the performance of the product. Therefore, the modified sol composition of the present invention is proprietary, and the effect of using other raw materials is not obvious. Only by using the raw materials of the present invention, the performance effect of the product is the most significant.
[0167] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0168] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A particle refining agent for 7 series aluminum-zinc alloy, characterized in that: It includes the following raw materials in parts by weight: 35-45 parts of potassium chloride, 10-15 parts of calcium fluoride, 7-11 parts of graphene modifier, 6-8 parts of modifier based on modified sol, 5-8 parts of magnesium chloride; The preparation method of the graphene modifier is: S01: Stir graphene in a sufficient amount of hydrogen peroxide solution to mix thoroughly, then wash, filter and dry; The dried graphene was heat treated at 150-160°C for 10-15 min, then heated to 300°C at a rate of 2-5°C / min, kept at that temperature for 10 min, and finally air-cooled to room temperature; S02: Preparation of additives: S021: first prepare a chitosan solution with a mass fraction of 3-5%; S022: adding 2 to 5 parts of cerium powder and 1 to 3 parts of sodium dodecylbenzene sulfonate to 5 to 8 parts of chitosan solution and stirring evenly, then adding 4 to 7 parts of nano carbon powder and blending thoroughly, then filtering and drying to obtain an additive; S03: adding 2 to 5 parts of silane coupling agent KH550, 1 to 3 parts of lanthanum chloride solution and 4 to 6 parts of additives to 5 to 8 parts of sodium silicate solution and stirring thoroughly to obtain a modified coupling solution; S04: the graphene of S01 is sent into a modified coupling liquid with a volume of 4 to 6 times the total volume of the graphene of S01 for ultrasonic modification treatment, and after the ultrasonic treatment is finished, the graphene is filtered and dried to obtain a graphene modifier; The preparation method of the modified sol-based toner is: S101: yttrium oxide and nano-silicon dioxide are fully mixed in a weight ratio of 2:(4-6), and then the mixture is placed in a sufficient amount of sodium alginate solution and dispersed evenly to obtain a yttrium-silicon compounding agent; S102: The modified sol and the yttrium-silicon compounding agent are mixed and ball-milled in a weight ratio of 3:5, with a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a toning agent based on the modified sol; the modified sol comprises the following raw materials in parts by weight: 3-5 parts of nano silica sol, 4-6 parts of dopamine hydrochloride solution, 2-3 parts of nano titanium dioxide, 0.4-0.5 parts of fly ash and 1-2 parts of stearic acid.
2. A particle refining agent for 7 series aluminum-zinc alloy according to claim 1, characterized in that: The particle refining agent comprises the following raw materials in parts by weight: 40 parts of potassium chloride, 12.5 parts of calcium fluoride, 9 parts of graphene modifier, 7 parts of a modifier based on modified sol, and 4 parts of magnesium chloride.
3. A particle refining agent for 7 series aluminum-zinc alloy according to claim 2, characterized in that: The mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the sodium silicate solution is 4-6%.
4. A particle refining agent for 7 series aluminum-zinc alloy according to claim 3, characterized in that: The ultrasonic power of the ultrasonic modification treatment is 350-400W, and the ultrasonic time is 20-30min.
5. A particle refining agent for 7 series aluminum-zinc alloy according to claim 4, characterized in that: The mass fraction of the sodium alginate solution is 5-8%.
6. A particle refining agent for 7 series aluminum-zinc alloy according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%.
Citation Information
Patent Citations
Bio-enzyme refining agent for graphite and composite fiber of graphite and use method of bio-enzyme refining agent
CN107083672A
Refining agent for waste aluminum to improve performance of aluminum castings
CN108179298A